ELECTRON PARAMAGNETIC RESONANCE STUDIES ON SOME TUTTON SALT SYSTEMS - Pant, Navin; Verma, Anandi Lal; Pandey, S. D. (Malaysian Journal of Science, 2020)
Abstract: Electron paramagnetic resonance (EPR) studies have been carried out on a vanadyl doped mixed Tutton salt (Zn0.25 Mg0.75(NH4)2(SO4)2.6H2O) system. The “g” and “A” parameters obtained from our studies are then compared with other vanadyl doped Tutton salts and a critical analysis is presented. As EPR results depend upon the neighborhood of V4+ of doped V=O ion in the host, the ‘g’ and ‘A’ parameters obtained from our studies reflect distorted octahedral surroundings of V4+ in the Tutton salt host and two major types of metal –water linkages are established. Our findings are supported by the X-ray studies and electric field assisted deaquation studies on Tutton salts by the earlier workers. Critical analysis and correlation of all the results indicate that the equatorial bonds and axial bonds between the oxygen of water molecules and the divalent cation in Tutton salts are different establishing that the octahedron formed by water molecules around the divalent ion in Tutton salts is distorted. Keywords: Tutton salt, EPR, X-ray studies, deaquation studies of Tutton Salts.